(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدف البحث إلى تحديد مستوى رضا العملاء عن أداء أعضاء قنوات التوزيع في شركة جود للأدوات المنزلية الكهربائية وفق الخصائص الآتية: الصدق والمسؤولية, والنواحي المعرفية, والمهارات, والعرض, والتفاوض. وذلك من خلال إجراء دراسة ميدانية تمّ من خلالها استهداف شريحة من العملاء الذين يقصدون منافذ توزيع الشركة. اعتمد البحث على المنهج الوصفي, وتكون مجتمع الدراسة من عملاء شركة جود للأدوات المنزلية والكهربائية, أما عينة الدراسة فهي عينة ميسرة من المجتمع السابق, حيث بلغت (200) مفردة, تمّ توزيعها على عملاء الشركة, وتمّ استرجاع (176) استبانة كاملة وصالحة للتحليل الإحصائي, وبنسبة استجابة بلغت (88%). تمّ تصميم "استبانة", وقد تكونت الاستبانة من (31) عبارة موزعة على خمس محاور شملت خصائص أعضاء قنوات التوزيع. توصل البحث إلى مجموعة من النتائج أهمها: أنّ مستوى رضا العملاء عن أداء أعضاء قنوات التوزيع فيما يتعلق بـ: الصدق والمسؤولية, والنواحي المعرفية, والمهارات, والعرض, والتفاوض, في شركة جود للأدوات المنزلية والكهربائية هو مستوى مرتفع. The objective of the research is to determine the level of customer satisfaction with the performance of the members of the distribution channels in Joud Company for electrical household appliances according to the following characteristics: honesty, responsibility, knowledge, skills, presentation and negotiation. Through conducting a field study through which a segment of the customers who are targeting the distribution outlets of the company were targeted. The sample of the study was a soft sample from the previous society. The sample consisted of (200) individual, distributed to the customers of the company, and 176 (complete questionnaire) were retrieved and valid for the statistical analysis , With a response rate of (88%). The questionnaire was designed from 31 words distributed on five axes that included the characteristics of the members of the distribution channels. The research reached a number of results, the most important of which is that the level of customer satisfaction with the performance of the members of the distribution channels regarding the level of honesty, responsibility, knowledge, skills, presentation and negotiation in Joud Company for household and electrical appliances is high.